Respuesta :
Answer:
Using the distance formula, when I plugged in the information, the answer I got was the square root of 85. (B)
explanation:
C(x₁ , y₁) and T(x₂ , y₂) OR C(0,4) and T(-6,-3)
CT=√[(x₂ - x₁)² + (y₂ - y₁)²] =√[(-6-0)² + (-3 - 4)²]
CT=√[(36) + (49)} = CT = √85
Answer:
Using the distance formula, when I plugged in the information, the answer I got was the square root of 85. (B)
explanation:
C(x₁ , y₁) and T(x₂ , y₂) OR C(0,4) and T(-6,-3)
CT=√[(x₂ - x₁)² + (y₂ - y₁)²] =√[(-6-0)² + (-3 - 4)²]
CT=√[(36) + (49)} = CT = √85
Hopefully this helps!!!